ANALYSIS OF EFFECTIVE PUBLIC FINANCE STRATEGIES TO TACKLE CLIMATE CHANGE - Mas, I Made Ade Widana Suartama (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2024)
This study emphasizes how important it is for public employees to use efficient public finance techniques to lessen the effects of climate change. In order to create a comprehensive climate action plan, the report highlights the significance of incorporating sustainability into government policy, obtaining sufficient funds, and promoting cooperation among diverse stakeholders. The study also emphasizes how citizen involvement can lead to significant change and how public-private partnerships can help close the financial gap for climate projects. The study intends to find chances for cooperation, enhance the efficacy of climate finance, and stimulate creative methods of resource mobilization in the face of urgent climate concerns by looking at case studies and best practices worldwide. The research concludes that public-private partnerships in climate finance can accelerate the achievement of climate goals. Collaboration between government, business and civil society is an important aspect of renewable energy, energy efficiency and carbon reduction. On the other hand, transparency, accountability and clear regulations are important to encourage trust in climate finance. By promoting a transparent culture, stakeholders can collaborate to realize a more environmentally friendly and responsible future. Keywords: Finance, Service, And Public